2017
DOI: 10.1186/s13075-017-1252-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex serum protein analysis reveals potential mechanisms and markers of response to hyperimmune caprine serum in systemic sclerosis

Abstract: BackgroundHyperimmune caprine serum (HICS) is a novel biological therapy with potential benefit for skin in established diffuse cutaneous systemic sclerosis. Here we report multiplex protein analysis of blood samples from a placebo-controlled phase II clinical trial and explore mechanisms of action and markers of response.MethodsPatients were treated with HICS (n = 10) or placebo (n = 10) over 26 weeks, with follow-up open-label treatment to 52 weeks in 14 patients. Serum or plasma samples at baseline, 26 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Indeed, ELF score and the single markers were significantly higher in patients with dcSSc, severe skin involvement, fibrosis on chest HRCT scan, abnormal pulmonary function and DLCO. The higher PIIINP level of patients on immunosuppressive therapy is consistent with published data and may reflect a higher level of ECM turnover (11). By contrast, ELF and the single markers showed no difference in patients with digital ulcers or with specific videocapillaroscopy patterns compared to patients without signs of severe vasculopathy.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, ELF score and the single markers were significantly higher in patients with dcSSc, severe skin involvement, fibrosis on chest HRCT scan, abnormal pulmonary function and DLCO. The higher PIIINP level of patients on immunosuppressive therapy is consistent with published data and may reflect a higher level of ECM turnover (11). By contrast, ELF and the single markers showed no difference in patients with digital ulcers or with specific videocapillaroscopy patterns compared to patients without signs of severe vasculopathy.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the 2 gene skin score biomarker was significantly reduced agree treatment with anti TGFbeta monoclonal antibody. In a trial of the novel biological agent HICS there were changes in serum markers that reflected the likely mechanism of action by stimulating the hypothalamopituitary axis and upregulating MSH which has antifibrotic activity in preclinical models [6]. There was a link between markers of fibrosis and clinical improvement in MRSS over 26 weeks in this clinical trial [7].…”
Section: Bio-sampling To Explore Treatment Mechanisms and Target Engamentioning
confidence: 83%
“…This was not seen in a study of imatinib, which instead showed no evidence of benefit for this treatment and evidence of substantial toxicity (31). In a trial of hyperimmune caprine serum, skin scores did improve and IL-6 was among the serum cytokines whose levels decreased during therapy, thereby indicating it as a possible marker of skin change (32).…”
Section: Il-6 Changes In Ssc Interventional Trialsmentioning
confidence: 99%